Paths to the Ancient Past. Applications of the Historical Method to Ancient History - Jones, Тоm В. (1967)
Archaeology; Decipherment; Literary Sources; Criticism, External and Internal; The Labyrinth of Chronos; A Word about Documents; Numismatics.